Fiscal Policy in the Spectrum As-Shari’ah Maqashid: Study of Al-Syatibi Thinking in the Book of Al-Muwafaqat - Marhalifams, Akmal (Li Falah: Journal of Islamic Economics and Business, 2023)
This study aims to determine fiscal policies within the spectrum of Maqasid Syariah al-Syatibi. The type of research used is qualitative research with the case study method, namely by reviewing various references that have developed in the biography, history, and writing of al-Syatibi in the al-Muwafaqat book. The result of this research is that in determining the fiscal policy of a country, it must be based on benefits, namely gold as the principle of public policy governance, fiscal policy for the welfare of the people, and taxation as the concept of economic equity. According to Al-Syatibi in al-Muwafaqat, none of Allah SWT's laws have no purpose because a law that has no purpose is the same as imposing something that cannot be implemented.